Patuntung Ilalang Embayya: Exposing Implicit Violence and Reducing Negative Stigma through Albert Ellis' Perspective - Muh. Syawal Hikmah; Akhmad Harum; Hastriani Rahayu; Eliana Eliana; Indah Putri; Faqih Hidayatullah (Universitas Muhammadiyah Malang, 2024)
The indigenous Kajang Ilalang Embayya community in Bulukumba, who adhere to the Patuntung faith, often face implicit violence such as negative stigma, discrimination, cultural norms, and social structures due to the conservatism of their local beliefs. This study aims to uncover the implicit violence experienced by Patuntung adherents, explore the existence strategies of the Patuntung belief system, and evaluate the effectiveness of cognitive disputation techniques in multicultural counseling from Albert Ellis' perspective to reduce negative stigma. This research uses a qualitative approach with an ethnographic design and quantitative statistical analysis to assess changes after the intervention. Data were collected through observations, in-depth interviews, and questionnaires, then analyzed using Atlas.Ti and JASP software. The results show that implicit violence stems from stigmatization, discrimination, cultural norms, and social structures, with 51.3% of respondents falling into the moderate category of committing implicit violence. The intervention using cognitive disputation techniques in multicultural counseling showed a significant reduction in negative stigma, as evidenced by the paired sample t-test with α: 0.001<0.05 and a t-value = 29.283 > t-table = 3.851. The study concludes that cognitive disputation techniques are effective in reducing negative stigma, contributing to efforts to preserve local conservatism amidst the implicit violence faced. Masyarakat adat Kajang Ilalang Embayya di Bulukumba, yang menganut kepercayaan Patuntung, sering menghadapi kekerasan implisit seperti stigma negatif, diskriminasi, norma budaya, dan struktur sosial akibat konservatisme kepercayaan lokal mereka. Penelitian ini bertujuan untuk mengungkap kekerasan implisit yang dialami oleh penganut Patuntung, mengeksplorasi strategi eksistensi kepercayaan Patuntung, serta mengevaluasi efektivitas teknik disputasi kognitif dalam konseling multikultural perspektif Albert Ellis untuk mengurangi stigma negatif. Penelitian ini menggunakan pendekatan kualitatif dengan desain etnografi serta analisis statistik kuantitatif untuk menilai perubahan setelah intervensi. Data dikumpulkan melalui observasi, wawancara mendalam, dan kuesioner, yang kemudian dianalisis menggunakan perangkat lunak Atlas.Ti dan JASP. Hasil menunjukkan bahwa kekerasan implisit berasal dari stigmatisasi, diskriminasi, norma budaya, dan struktur sosial, dengan 51,3% responden berada dalam kategori sedang melakukan kekerasan implisit. Intervensi menggunakan teknik disputasi kognitif dalam konseling multikultural menunjukkan penurunan signifikan dalam stigma negatif, dibuktikan melalui uji t berpasangan (paired sample t-test) dengan α: 0,001<0,05 dan hasil t hitung = 29,283 > t-tabel = 3,851. Kesimpulannya, teknik disputasi kognitif efektif dalam mengurangi stigma negatif, serta mendukung upaya mempertahankan konservatisme lokal di tengah kekerasan implisit yang dihadapi.